2009
DOI: 10.1038/npp.2009.84
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Alpha-Linolenic Acid Treatment Enhances Brain Plasticity and Exerts an Antidepressant Effect: A Versatile Potential Therapy for Stroke

Abstract: Omega-3 polyunsaturated fatty acids are known to have therapeutic potential in several neurological and psychiatric disorders. However, the molecular mechanisms of action underlying these effects are not well elucidated. We previously showed that alpha-linolenic acid (ALA) reduced ischemic brain damage after a single treatment. To follow-up this finding, we investigated whether subchronic ALA treatment promoted neuronal plasticity. Three sequential injections with a neuroprotective dose of ALA increased neurog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 71 publications
8
84
0
1
Order By: Relevance
“…Omega-3 is known to play a role in the regulation of neurotrophins like BDNF and its receptor Trk-B, which are involved in spatial learning and memory (Bhatia et al 2011). Several studies have reported enhanced hippocampal neurogenesis along with increased levels of BDNF levels following omega-3 PUFAs treatment (Blondeau et al 2009, Venna et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Omega-3 is known to play a role in the regulation of neurotrophins like BDNF and its receptor Trk-B, which are involved in spatial learning and memory (Bhatia et al 2011). Several studies have reported enhanced hippocampal neurogenesis along with increased levels of BDNF levels following omega-3 PUFAs treatment (Blondeau et al 2009, Venna et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Subchronic treatment with three sequential injections of LIN has been previously demonstrated to increase the endogenous expression of mature brain-derived neurotrophic factor (BDNF) levels in neural stem cells, cultured hippocampal neurons and in cortex and hippocampus. Also in cortex and hippocampus, LIN increases synaptogenesis, synaptic function and increases neurogenesis in the subgranular zone of the dentate gyrus of the hippocampus in naïve mice (Blondeau et al 2009). This treatment schedule also significantly reduced infarct volume in the middle cerebral artery occlusion model of stroke and was associated with a significant improvement in animal survival (Blondeau et al 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported enhanced hippocampal neurogenesis in parallel with increase levels of BDNF levels following omega-3 PUFA treatment (Cysneiros et al, 2010;Venna et al, 2009;Blondeau et al, 2009). For example, three sequential injections of alinolenic acid significantly enhances adult hippocampal neurogenesis in mice, and increases in the expression of BDNF in hippocampal neurons and cortical and hippocampal tissue (Blondeau et al, 2009). In this study, the treatment also significantly increases the expression of proteins critical for synaptogenesis and synapse function, syntophysin-1, VAMP-2 and SNAP-25, and proteins supporting glutamatergic neurotransmission, V-GLUT-1 and V-GLUT-2.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%